Piomi Efektif dalam Meningkatkan Kesiapan Minum Bayi Premature - Fitriyati, Fitriyati; Sutini, Titin; Purwati, Nyimas Heny; Srisantyorini, Triana; Sulistiawati, Helda (Universitas Malahayati, 2024)
ABSTRACT The incidence of premature births is still quite high along with complex health problems in premature babies caused by immaturity of the body's organ systems in premature babies and babies born prematurely lacking the ability to suck and swallow which is related to the baby's readiness to drink. The aim of the research is that Piomi is effective in increasing the drinking readiness of premature babies. Research design. This research uses a quasi-experimental research design with a pre test and post test with control group with two types of intervention. Results The results of this research show that there is a significant difference between the pre and post interventions of PIOMI and Multistimulation. on the baby's drinking readiness (P value <0.05). There was also an influence between the PIOMI and Multistimulation interventions on the baby's drinking readiness (P value <0.05). The conclusion shows that there is a difference in the level of readiness to drink babies before and after the PIOMI intervention, as well as in the Multistimulation intervention group. Difference PIOMI Intervention is more effective than Multisimulation Intervention. Keywords: Premature Babies, Baby Drinking Readiness, PIOMI, Multistimulation ABSTRAK Angka kejadian kelahiran prematuritas masih cukup tinggi beserta permasalahan yang kompleks permasalahan kesehatan pada bayi prematur disebabkan oleh ketidakmatangan sistem organ tubuh pada bayi prematur dan bayi yang lahir dalam kondisi prematur kurang memiliki kemampuan menghisap dan menelan yang berhubungan dengan kesiapan minum bayi. Tujuan penelitian diketahui piomi efektif dalam meningkatkan kesiapan minum bayi premature Desain penelitian Penelitian ini menggunakan rancangan penelitian quasi eksperiment dengan pre test dan post test with control group dengan dua macam Intervensi.Hasil Hasil penelitan ini menunjukkan ada perbedaan yang signifikan antara pre dan post intervensi PIOMI danMultikstimulasi terhadap kesiapan minum bayi (P value<0,05).Terdapat juga pengaruh anatara Intervensi PIOMI dan Multistimulasi terhadap kesiapan minum bayi (P value<0,05). Kesimpulan menunjukan bahwa terdapat perbedaan tingkat kesiapan minum bayi sebelum dan sesudah dilakukan Intervensi PIOMI, begitupula da kelompok intervensi Multistimulasi. Perbedaan Intervensi PIOMI lebih efektif dibanding Intervensi Multisimulasi. Kata Kunci: Bayi Prematur, Kesiapan Minum Bayi, PIOMI, Multistimulasi